Does Management Practice Lag Behind Theory in the Computer Environment? - Moan, Floyd Edward (Academy of Management Journal, 1973)
The effect of the computer on management practice and management style in the field of inventory control is investigated in five selected major corporations. Despite the large expenditure of money and technical talent, top management rarely uses the computer effectively. A method of measuring the organization's ability to adapt to the computer environment is described.